Package of local interventions for reducing in-hospital neonatal mortality using quality improvement methodology at a major hospital in India - Soni, Prashant; Yadav, Mukesh; Choudhary, Neelam (International Journal Of Community Medicine And Public Health, 2017)
Background: Reducing neonatal mortality has always been a challenge for the world and India. Here we provide a brief account of a pilot done at Sanjay Gandhi Memorial Hospital, New Delhi for reducing neonatal mortality. Methods:Rotation of labour room nurses to In-hospital Neonatal ICU for a specified period of 4 months for providing hands-on training on neonatal emergencies. In exchange, equal number of Nurses from NICU was posted in labour room, thus making each delivery managed by an obstetric nurse and a paediatric nurse. Ensuring breastfeeding within one hour within the labour room itself was also mandated by NICU Nurse. Results: It was observed that there was 30.2% decrease in In-hospital neonatal mortality. Conclusions:Using these interventions, there has been a dramatic decrease of neonatal mortality to 30.2% and 4.53% due to sepsis. There has also been 1% decrease in Median Referral Percentage to In-hospital Neonatal ICU due to morbidities associated with inborn neonates.